Circulating Trimethylamine-N-Oxide and Risk of All-Cause and Cardiovascular Mortality in Patients With Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Zhou, Zhongwei; Jin, Hao; Ju, Huixiang; Sun, Mingzhong; Chen, Hongmei; Li, Li (Frontiers in Medicine, 2022)
Background: Trimethylamine-N-oxide (TMAO) is expected to be a prognostic biomarker among patients suffering from chronic kidney disease (CKD). However, investigations on the association between TMAO and CKD prognosis are conflicting. In the present paper, we aimed to assess the relationship of circulating TMAO with the risk of all-cause and cardiovascular mortality among CKD patients by a meta-analysis. Methods: Data were collected from PubMed, EMBASE, and Web of Science for systematically searching related literature (last update: February 2022). The multivariable-adjusted hazard risks (HR) and their 95% confidence intervals (CI) were pooled using random effects models. Results: Eleven prospective cohort studies covering 7899 CKD patients were enrolled in this meta-analysis. When comparing individuals in the top and bottom baseline TMAO levels thirds, the multivariate adjusted pooled HR was 1.29 (95% CI 1.11-1.51, P = 0.001) for all-cause mortality, and 1.45 (95% CI 1.01-2.09, P = 0.043) for cardiovascular death. For continuous variables, per 1 unit increase of circulating TMAO levels was associated with a 3% higher all-cause mortality (HR 1.03, 95% CI 1.00-1.06, P = 0.032), but not significantly associated with cardiovascular death (HR 1.08, 95% CI 0.92-1.27, P = 0.346). Stratified analyses revealed that the positive relationship between TMAO and all-cause mortality remained significant after adjusting for diabetes, blood pressure, blood lipid, renal function, or inflammatory parameters. Conclusions: Higher circulating TMAO was associated with an increased mortality risk among patients with CKD, and this relationship may be dependent on TMAO dose and independent of renal function, inflammation, diabetes, hypertension, and dyslipidemia.